Deleuze's difference and repetition - Hughes, Joe (London Continuum, 2009)
This is a Reader's Guide to arguably Deleuze's most demanding work and a key text in modern European thought.Gilles Deleuze is without question one of the most influential thinkers of the twentieth century. "Difference and Repetition" is a classic work of contemporary philosophy and a key text in Deleuze's oeuvre, a brilliant exposition of the critique of identity that develops two key concepts: pure difference and complex repetition. "Deleuze's 'Difference and Repetition': A Reader's Guide" offers a concise and accessible introduction to this hugely important and yet notoriously demanding work. Written specifically to meet the needs of students coming to Deleuze for the first time, the book offers guidance on: Philosophical and historical context; Key themes; Reading the text; Reception and influence; And, further reading."Continuum Reader's Guides" are clear, concise and accessible introductions to key texts in literature and philosophy. Each book explores the themes, context, criticism and influence of key works, providing a practical introduction to close reading, guiding students towards a thorough understanding of the text. They provide an essential, up-to-date resource, ideal for undergraduate students.